Effect of Portland Cement, Silica Fume, Fly Ash Combinations On Pressurized Water Permeability of Self-Compacting Mortars - Turgut, Paki; Türk, Kazım; Çekilmez, Nuray (Fırat University, 2019)
The water permeability has great importance with respect to durability for concrete structures subjected to pressure and mortars used in construction and repair of water tanks, dam structures, and some industrial buildings. In this work, the water permeability under pressure was investigated in binary and ternary self-compacting mortars with Portland cement, silica fume and fly ash, and at their combinations. Water penetration depths were determined in these samples. The water penetration depths were decreased in the binary sample containing Portland cement and 10% silica fume, and the ternary sample containing Portland cement, 10% silica fume and 35% fly ash.

Su depolarında, baraj yapılarında, bazı endüstriyel binaların yapımında ve onarımında kullanılan beton ve harçların, basınçlı su geçirgenliği değeri dayanıklılık bakımından büyük öneme sahiptir. Bu çalışmada, Portland çimentosu, silis dumanı ve uçucu kül içeren ikili ve üçlü kendiliğinden yerleşen harçlarda ve bunların kombinezonlarından oluşan numunelerde basınçlı su geçirgenliği araştırılmıştır. Bu örneklerde baınçlı su işleme derinliği belirlenmiştir. Portland çimentosu ve %10 silis dumanı içeren ikili numunede, Portland çimentosu, %10 silis dumanı ve %35 uçucu kül içeren üçlü numunede basınçlı su geçirgenliği değerleri azaltılmıştır.
Kendiliğinden Yerleşen Harçlarda Portland Çimentosu, Silis Dumanı, Uçucu Kül Kombinezonlarının Basınçlı Su Geçirgenliğine Etkisi